RoboSpy: Autonomous Night Vision Surveillance Robot with Spying Camera for War Field Operations - S., Jeffrey Sham R; G., Yashwanth M; Y, Vamshi Krishna (Journal of Electrical Engineering and Automation, 2025)
RoboSpy is an autonomous surveillance robot designed for war field operations, equipped with night vision capabilities and a spying camera. Its primary goal is to provide real-time intelligence, enhance situational awareness, and reduce risks to soldiers by conducting reconnaissance in hazardous conditions. RoboSpy integrates advanced sensors, hardware, and software to navigate complex environments, detect obstacles, and transmit critical data to remote operators. The system architecture features a Raspberry Pi as the processing unit, ultrasonic sensors to detect objects, and a high-resolution night vision camera for real-time video capture. The software utilizes an intelligent HAAR Cascade classifier algorithm for object detection, path planning algorithms for navigation, and enhanced image processing techniques to capture the moving image. The RoboSpy provides real-time support for security forces to monitor the movement of intruders in the restricted area. This research discusses the design, implementation, and potential military applications of RoboSpy, emphasizing its role in reducing human intervention during high-risk reconnaissance missions.